2023
DOI: 10.1177/20406207231179331
|View full text |Cite
|
Sign up to set email alerts
|

Real-world patient characteristics and treatment patterns of polycythemia vera in Taiwan between 2016 and 2017: a nationwide cross-sectional study

Abstract: Background: Polycythemia vera (PV) patients often experience constitutional symptoms and are at risk of thromboembolism as well as disease progression to myelofibrosis or acute myeloid leukemia. Not only is PV often overlooked but treatment options are also limited, however. Objectives: To explore the patient characteristics and treatment pattern of PV patients in Taiwan, and compare with other countries reported in the literature. Design: This is a nationwide cross-sectional study. Methods: The National Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Of which, reducing the risks of thrombosis and disease progression are especially important from the perspective of patients [ 129 ]. However, a real-world nationwide study in Taiwan showed that around 48.8% low-risk and 26.1% high-risk PV patients were not undergoing active treatment [ 130 ]. Additionally, another study in the United States based on a veteran database reported that 53% of patients were not receiving active treatment [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of which, reducing the risks of thrombosis and disease progression are especially important from the perspective of patients [ 129 ]. However, a real-world nationwide study in Taiwan showed that around 48.8% low-risk and 26.1% high-risk PV patients were not undergoing active treatment [ 130 ]. Additionally, another study in the United States based on a veteran database reported that 53% of patients were not receiving active treatment [ 131 ].…”
Section: Discussionmentioning
confidence: 99%